Upaya PKBM KH Asyikin Sebagai Agen Perubahan Sosial dalam Mewujudkan Kesetaraan Pendidikan - Mahmud, Imam; Raidar, Usman; Dewi Ayu Hidayati; Teuku Fahmi (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to analyze the role of PKBM KH Asyikin (Community Learning Center) as a social change agent in enhancing educational access and equity for students (santri) within the Islamic boarding school (pesantren) environment. The research was conducted at Pondok Pesantren Darussa’adah in Bandar Lampung using a qualitative descriptive approach. Data were collected through participatory observation, in-depth interviews with administrators, teachers, and students, as well as documentation of educational activities. The findings show that the Community Learning Center plays a strategic role in expanding opportunities for santri to pursue higher education through intensive preparatory learning and strong social support. However, challenges such as low motivation among non-santri participants, limited learning infrastructure, and gaps in academic readiness persist. This study highlights the importance of synergy between nonformal education institutions and Islamic boarding schools in realising more inclusive and sustainable access to higher education